Food processing trout aquaculture and processing - Satterlee, Lowell D. (Penn Media Sales, 1992)
Explains how fingerling trout (fry) are farmed in captivity. Shows the fry as they go through their growth cycle at a fish farm, their transportation as adult trout to a processing facility, the procedures used to ready them for market: including dressing (removing the GI tract and gills), in the round (where the GI tract is left intact), and filleting (the most common method), and finally packaging the trout for display on ice.